Quality-enabled decentralized IoT architecture with efficient resources utilization. (February 2021) - Mocnej, Jozef; Pekar, Adrian; Seah, Winston K.G.; Papcun, Peter; Kajati, Erik; Cupkova, Dominika; Koziorek, Jiri; Zolotova, Iveta
Highlights: We propose a representation model for IoT network quality monitoring at runtime. We present a quality-enabled framework for efficient resources utilization. We identify a desired feature set for decentralized IoT architectures. We design a quality-enabled decentralized IoT architecture. We evaluate the proposed architecture via a series of case studies. Abstract: The Internet of Things (IoT) is a paradigm aimed at connecting everyday objects to the internet. IoT applications include smart cities, healthcare, agriculture, as well as the industry and manufacturing. The ability to monitor and control the physical world using information technology creates many opportunities. However, it also comes with some costs. The exponential growth of connected devices, the heterogeneity of IoT use cases, and the diversity of the network technologies yield a concern regarding IoT sustainability. With this work, we aim to contribute to this concern. In doing so, we introduce a novel representation model that is destined for (i) monitoring the IoT environment at runtime, (ii) expressing the overall quality of the system, and (iii) helping to utilize the available resources efficiently. We also define a feature set that describes the best the expectations of decentralized IoT platforms. Furthermore, we describe a quality-enabled decentralized IoT architecture too that incorporates the specified feature set as well as our representation model. Such solutions are necessary to improve and maintain IoT of the future and all its application domains, including the Industrial Internet of Things (IIoT). With the presented research, we aim to encourage the efficient utilization of resources and simplify the production of next-generation IoT solutions.